Microglial activation and brain networks in Alzheimer's disease: The ActiGliA cohort study: Neuroimaging / Multi‐modal comparisons. (7th December 2020) - Rauchmann, Boris‐Stephan; Brendel, Matthias; Keeser, Daniel; Tato, Maia; Palleis, Carla; Zaganjori, Mirlind; Ersözlü, Ersin; Janowitz, Daniel; Bürger, Katharina; Goldhardt, Oliver; Grimmer, Timo; Levin, Johannes; et al.
Abstract: Background: Recent research suggests that brain network degeneration and immune response play important roles in Alzheimer's Dementia (AD). Brain network connectivity become increasingly impaired as AD progresses. Glial activation in the neuropathology of AD has also been widely recognized both as a consequence and as a contributing factor for the formation of Aβ and tau aggregation. Immune surveillance in the brain and microglial activation can be reliably measured by translocator protein (TSPO) positron emission tomography (PET). Method: To understand better important associations between network degeneration and immune response in AD, we initiated the ActiGliA prospective cohort study. Here we present an analysis of the initial 55 participants, including 20 participants with subjective cognitive declined, 19 patients with mild cognitive impairment and 16 AD patients. Participants were characterized using CSF biomarker information and underwent TSPO‐PET, fMRT and DTI acquisitions. We assessed topographical associations between microglia activity (TSPO‐PET covariance) with resting state functional and DTI structural connectivity changes using a 210 regions parcellation of the neocortex. PET and MRI preprocessing were performed using standard imaging pipelines. Result: At baseline, elevated microglia activity was found in TSPO‐PET analysis of AD patients. Resting state fMRI graph‐theory analysis showed reduced global efficiency and increased local efficiency in AD compared to controls. No significant group differences were found in the graph‐theory analysis of structural connectivity. In a further analysis, we assessed the association between microglia activity and functional connectivity. A positive correlation of resting state functional connectivity with microglia covariance (r=0.177, p<0.001), but no correlation of structural connectivity and microglia covariance were detected. Network specific TSPO uptake in resting‐state networks, demonstrating increased uptake in the language, default mode network (DMN), and visual network in the AD group compared to controls. Conclusion: In line with previous findings, we confirm that brain functional connectivity is disrupted and microglial activity is elevated in AD. Preliminary results suggest an association between functional connectivity and microglia activity in AD, furthermore microglia activity is preferentially found in particular resting state networks.